Social Media Marketing and Purchasing Decision among Generation Z consumers - Patrixia Gliezel Torres; Priyono Joko Alam; Lela Nurlaela Wati (Research Synergy Foundation, 2023)
This research identified strategies that enable small and medium-sized enterprises (SMEs) to leverage social media to engage Generation Z consumers. Understanding how SMEs utilize social media and implement best practices is crucial for fostering business-to-consumer relationships. The study assessed the utilization of social media marketing, specifically electronic word-of-mouth (eWOM), trust, and the level of purchasing decision factors (awareness, interest, desire, and action) among Generation Z consumers in Los Baños, Laguna. The findings reveal that social media marketing, particularly eWOM, was fully utilized by Generation Z consumers in Los Baños, Laguna, indicating its significance in influencing their purchasing decisions. This research used a quantitative research design with a total of 380 respondents of Generation Z residing in Los Baños, Laguna. The instrument used was an adopted survey questionnaire previously validated by the researcher, which is to be improved and further validated by the adviser. This research provides valuable insights into the relationship between social media marketing and Generation Z consumers' purchasing decisions. Understanding and leveraging these insights can help businesses engage with this influential consumer segment and drive business growth in the digital age.